2012
DOI: 10.1111/j.1600-0838.2011.01439.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of double‐ vs single‐bundle anterior cruciate ligament reconstruction: A systematic review of randomized control trials

Abstract: Clinical outcomes of anterior cruciate ligament (ACL) reconstruction with double-bundle and single-bundle techniques are still controversial. We therefore performed a systematic review to compare postoperative outcomes between the two techniques. Randomized control trials comparing the outcomes between the two techniques were identified from Medline and EMBASE since inception to April 27, 2011. Data were independently extracted by two reviewers. Thirteen of 318 studies were eligible; 9, 11, 7, and 8 studies we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
45
0
4

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 49 publications
0
45
0
4
Order By: Relevance
“…4,6-9,14-17 Only 2 studies reported a potential conflict of interest. 14,16 Three of the studies included Level I Evidence only, 16,18,19 and 6 included Level I and Level II Evidence. [12][13][14][15]17,20 The studies included from 754 patients 16 to 1,686 patients, 17 with mean follow-up of studies included in the metaanalyses ranging from 5 months 25 to 103 months.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…4,6-9,14-17 Only 2 studies reported a potential conflict of interest. 14,16 Three of the studies included Level I Evidence only, 16,18,19 and 6 included Level I and Level II Evidence. [12][13][14][15]17,20 The studies included from 754 patients 16 to 1,686 patients, 17 with mean follow-up of studies included in the metaanalyses ranging from 5 months 25 to 103 months.…”
Section: Resultsmentioning
confidence: 99%
“…[12][13][14][15][16][17][18][19][20] These studies were published between 2008 and 2014, with all 9 performing a meta-analysis. 4,6-9,14-17 Only 2 studies reported a potential conflict of interest.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations